The Effect of the Kampus Mengajar Program on English Education Students’ Teaching Skills: A Comparative Study - Safitri, Anisa Nurul; Fatmawati, Rini (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – This study aims to review the Effect of the Kampus Mengajar Program on the Teaching Skills of English Language Education Students of the 2021 intake at Universitas Muhammadiyah Surakarta. This initiative offers direct teaching practice in schools, which is expected to improve their pedagogical competence.Method – The sample consisted of 54 participants from batches 5, 6, and 7, using a descriptive-comparative quantitative approach with a retrospective pretest-posttest design. Data collection used a closed questionnaire with a Likert scale. The questionnaire consisted of 21 indicators: 15 questions based on the microteaching approach of Allen & Cooper (1972) and 6 questions based on the CLT theory of Richards (2006). Technical data analysis was conducted using SPSS software version 24 for Windows.Findings – The results of the study, based on the Wilcoxon signed-rank test, indicate that (1) students’ teaching skills during the pretest are at the developing level with an average score of 3.05; (2) teaching skills after the posttest increase to the proficient category with an average score of 3.73; and (3) there is a significant difference between the pretest and posttest results, as shown by the Z value = -4.711 with Asymp. Sig (2-tailed) = 0.000 < 0.05. Research Implications – These findings highlight the importance of experiential learning programs in enhancing the pedagogical competencies of English education students. However, the sample size is small, and the use of self-perception means that further research is recommended to use a mixed approach with a wider sample.